Comportamento alimentar, padrão de atividades e uso do espaço por Alouatta fusca (Primates, Platyrrhini) em um fragmento degradado de Floresta Atlântica no Estado do Rio de Janeiro - Garcia, Vânia Luciane Alves (1996)
During 12 months, a wild group of four individuals (1 adult male, 1 undermale and 2 adults females ) of Alouatta fusca was followed for five days each month, in a 80 ha fragment of secondary forest located in the County of Comendador Gasparian, in the State of Rio de Janeiro. A phenological study of 320 trees in the area was performed concomitantly. The monkeys' feeding behavior, activity patterns, and home range were registered by scan sampling every three minutes, with 7-minute intervals. Fifty-eight complete days of observation were analyzed, totaling 700 hours of direct observation with 13,715 behavioral records taken. The daily movements of the group were measured after the behavioral observations were taken. The diet included leaves (72%), fruits (12%) and flowers (10%). Significant differences were detected between percentages in the use of leaves and flowers among seasons. Leaf consumption was greater in the Autumn and Winter. Flower comsumption was greater in the Spring and in the Summer. The group spent 73% of the day resting, 15% feeding, 11 % moving, 0.48% in social interactions, 0. 14% drinking, O, 11 % vocalizing, and O, 78% performing other activities. There were significant seasonal differences in the amount of time spent resting, feeding, and moving. ln the Summer, the group spent more time foraging, and less time resting or moving, whereas in the winter it spent less time feeding and more time resting and moving. Homerange was 11.6 ha, the largest recorded for this species to date. ln the Winter and in the Autumn the number of 25x25m squares used was significantly larger than in the Summer and in the Spring. Generally, the percentage of items in the diet and patterns of activity of the group were similar to the patterns observed in other study areas. Nevertheless, some seasonal differences have been observed, part of which may be related to the low plant diversity due to the accentuated level of forest fragmentation, and to the availability, distribution, density and phytochemical content of the plant resources.